The Effect of Hard Skills, Soft Skills, and Fieldwork Practice Experience on Job Readiness of Vocational Students - Syafira, Mauliana; Achmadi, Taofan Ali; Ihsani, Ade Novi Nurul; Nurhayati, Ifa (Universitas Negeri Semarang, 2025)
The era of the Industrial Revolution 4.0 requires vocational students to have work readiness to master hard skills, soft skills, and relevant fieldwork experience. This study aims to analyze the effect of hard skills, soft skills, and fieldwork practice (PKL) on the work readiness of vocational students in facing the challenges of Industry 4.0. The research method used is quantitative with a descriptive approach and multiple linear regression, involving vocational students as research subjects. The sampling technique used in this study is random sampling. The data collection method used was a survey using a questionnaire. The results showed that hard skills have a significant effect on work readiness, and soft skills have a significant effect on work readiness. In addition, the PKL experience positively contributes to increasing students' work readiness by providing direct experience in the industrial world.